The genus Leucophenga (Diptera, Drosophilidae), part VIII: twenty-one species from the Oriental region, with morphological and molecular evidence - Huang, Jia; Wang, Yalian; O’grady, Patrick Michael; Su, Yirui; Chen, Hongwei (Zootaxa, 2018)
Twenty-one (six known and 15 new) species of the genus Leucophenga from the Oriental region are described or redescribed: L. jacobsoni Duda, 1926; L. kurahashii Okada, 1987; L. setipalpis Duda, 1923; L. sorii Kang, Lee & Bhang, 1965; L. spinifera Okada, 1987; L. varinervis Duda, 1923; L. acantha Huang & Chen, sp. nov.; L. alafumosa Huang & Chen, sp. nov.; L. brevipenis Huang & Chen, sp. nov.; L. brevitabulata Huang & Chen, sp. nov.; L. delta Huang & Chen, sp. nov.; L. forcipula Huang & Chen, sp. nov.; L. fuscipalpula Huang & Chen, sp. nov.; L. glabtabulata Huang & Chen, sp. nov.; L. helvipecta Huang & Chen, sp. nov.; L. hyaloptera Huang & Chen, sp. nov.; L. oxyptera Huang & Chen, sp. nov.; L. platypyga Huang & Chen, sp. nov.; L. serrateiceps Huang & Chen, sp. nov.; L. valvata Huang & Chen, sp. nov.; L. zebrina Huang & Chen, sp. nov. A key and a morphological summary table to all these Leucophenga species are provided. Phylogenetic relationships among these 21 Leucophenga species, another 14 congeneric, known species from seven groups, and two representative outgroup taxa are reconstructed using 169 DNA sequences of the partial mitochondrial cytochrome c oxidase subunit I (mtCOI) gene. In sum, 13 of the 21 Leucophenga species, which possess the only diagnostic character of the proxima species group (abdominal third tergite shortened, anteriorly discolored in males), are not monophyletic. Therefore, all the Leucophenga species described or redescribed in this study are temporarily classified as unplaced species (except for L. sorii, which has been assigned to the sorii species group) to avoid further confusion.